Models of competition between firms: The case of Slovenia's (post)transitional economy - Tomaz Cater; Danijel Pucko (Journal for East European Management Studies, 2006)
The process of competition between firms can be described as a causalconsecutive sequence. The paper is built on the findings of empirical research based on a sample of 225 Slovenian firms. By using statistical methods we examine which approaches firms use to ensure their competitiveness and, based thereon, offer a judgement on the existence of potential models of competition in a posttransitional Slovenian economy. We conclude that there are four such models. They mainly differ in the sources of competitive advantage, financial and nonfinancial performance, size of firms and firms' strategies, whereas differences regarding the forms of competitive advantage are much less significant. Slovenian firms are therefore taking different paths towards competitiveness, which is not very surprising given the complexity of the competition process. – – Der Prozess von Wettbewerb zwieschen Firmen kann als kausal-konsekutiver Ablauf beschrieben werden. Dieser Aufsatz basiert auf dem Ergebnis der empirischen Untersuchung von 250 slowenischen Firmen. Durch die Anwendung statistischer Methoden untersuchen wir, welche Firmen sich eine Wettbewerbsfähigkeit sichern und darauf basierend bieten wir eine Beurteilung über die Existenz potentieller Wettbewerbsmodelle in der post-transitionellen slowenischen Wirtschaft. Wir schliessen darauf auf 4 Modelle. Sie unterscheiden sich in den Ursachen des Wettbewerbsvorteils, finanzielle und nichtfinanzielle Leistung, Firmengröße und -strategien, wobei Unterschiede bezüglich derFormen des Wettbewerbsvorteils zu vernachlässigen sind. Slowenische Firmen schlagen demzufolge verschiedene Wege zur Wettbewerbsfähigkeit ein, was nicht überraschend angesichts derKomplexität des Wettbewerbsprozesses ist.
Keywords: 650; firm; sources of competitive advantage; forms of competitive advantage; performance; models of competition